Avaliação multidimensional de um programa de intervenção com mães de crianças com deficiência - Azevedo, Tássia Lopes de (2014)
Involving families in intervention programs supports them and allows them to have autonomy to hire services while learning and strategizing the necessary requirements to claim their rights, as well as assist in the development or enhancement of skills to stimulate their children. The research aimed to implement a program of intervention with mothers of children with disabilities and to evaluate the influence of the same on the identification of needs, stimulation offered to children, stress level and level of empowerment. The intervention program occurred in nine weekly meetings, 120/150 minutes long, being divided into two parts: (a) parenting practices and child development and (b) thematic interests of mothers. All sessions were recorded wiht annotation into a field journal. To meet the goals, the mothers were evaluated through a resources and stress questionnaire, an EC-Home inventory and a family empowerment scale. In addition, the participants responded to questionnaires for evaluating the intervention framework to assess different aspects of the quality of the intervention, at the end of each meeting and the end of the program. To compare the averages of the mothers between the pre- and post-test Mann-Whitney test was used. To compare the frequency of stimulation that mothers offered children in the family environment, through the EC-Home Inventory, the Kruskal-Walllis was used. To relate the variables the Spearman correlation test was used, considering only the data of the pretest. The assessment tools and intervention sessions quantitative and qualitative data were obtained, which were calculated averages, standard deviation and content analyses performed. Based on the results, it was found that at every meeting, mothers were able to demonstrate their difficulties and potential to deal with some situations, express their feelings, exchange information and clarify their doubts in respect to the child with the disability. According to the results, there is statistically a significant decrease of the needs, and the level of family stress, as well as an increase in stimulation offered to the child in the family environmentt and empowerment. The higherthe age of the child, the greater the needs of families the higher the purchasing power of families, the greater the level of empowerment, and the lower the family stress. In regards to the structure of the intervention program, all aspects of the meetings were evaluated by the participants in a positive way, with scores ranging from 4.0 'good' to 5.0 'very good'. The most well assessed in different encounters were the speaker's ability to conduct the session in an orderly manner and that the participants had the opportunity to speak. The positive aspects of the intervention program were the mothers who showed that the Group clarified the doubts of participants and helped resolve difficulties related to the needs of children, On the other hand, the time when the subject was broached, evaluated by the mothers as short and the participation of the same were evaluated as a negative point of the intervention. It is concluded that the intervention program provided the mothers with the tools and information that might assist in family interactions, more specifically on the interactions between parents and children. It is believed that the participation of mothers in the intervention program can assist positively in the development of children with disabilities.